2015
DOI: 10.1002/ajpa.22914
|View full text |Cite
|
Sign up to set email alerts
|

Optimal trait scoring for age estimation

Abstract: The results from the analysis of the Todd pubic symphysis scores show that researchers should use goodness-of-fit tests for parametric models before deciding to collapse scores. Further, such goodness-of-fit tests are an essential tool in answering questions concerning the suitability of various parametric models. For the 15-stage scoring of the second mandibular molar, the log-normal model is appropriate for attainment ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 122 publications
(155 reference statements)
0
29
0
Order By: Relevance
“…Although Konigsberg et al. found that the second mandibular molar had a high probability value from the Lagrange multiplier test against log‐normal distributed ages of attainment, such was not true for the third molar. It is for this reason that we had to fit the more complicated unrestricted cumulative probit.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Although Konigsberg et al. found that the second mandibular molar had a high probability value from the Lagrange multiplier test against log‐normal distributed ages of attainment, such was not true for the third molar. It is for this reason that we had to fit the more complicated unrestricted cumulative probit.…”
Section: Resultsmentioning
confidence: 97%
“…These values were obtained from probit regression in the R package “VGAM.” The estimated mean and standard deviation for age‐of‐attainment are 19.41 and 1.83 years, respectively. The probability value on a Lagrange multiplier test for normality of the attainment ages is p = 0.4342. This is a goodness‐of‐fit test indicating that there is a strong basis for arguing that the unobserved distribution of attainment ages is indeed normally distributed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Konigsberg et al . () found that such a model often fits ordinal categorical data dependent on age. In particular, they found that this model fit well to cross‐sectional observations on dental formation following the Moorrees et al .…”
Section: Methodsmentioning
confidence: 99%